Parrots of Africa, Madagascar and the Mascarene Islands : biology, ecology and conservation - Perrin, Mike (Mike R.) (Wits University Press, 2012)
Parrots' colour and charisma, coupled with the fact that they mimic human speech, make them fascinating to many people. They are ancient birds with unique bill and foot structures that enable them to forage on fruits in the canopy of forest trees as well as on seeds in grasslands. Because they depend on fruits and seeds all year round, most species are confined to the tropics or subtropics, where the world's biodiversity is at its greatest. There are over three hundred species of parrots, of which more than one hundred are recognised as rare, endangered, vulnerable or threatened with extinction. Parrots are largely distributed in tropical areas of developing countries where economies are weak and uncertain, and where there is great dependence on the exploitation of natural resources, particularly hard wood evergreen forests, which are preferred parrot habitats. Unfortunately, high levels of corruption are common to these regions, with much illegal trade in animals and little or no law enforcement. Collectors of parrots in the first world pay huge sums for rare parrots. However, research, education and conservation actions are greatly reducing illegal trade in African parrots. This book provides complete coverage of all aspects of the biology of extant African, Malagasy and Mascarene parrots, and reviews our knowledge of extinct and fossil parrots from the region. Particular themes include the behavioural and ecological characteristics of parrots, their species characteristics and conservation biology. Current concepts in avian and conservation biology are also discussed. Parrots of Africa, Madagascar and the Mascarene Islands is aimed at ornithologists, conservation biologists, avian ecologists, academics, bird watchers and parrot fans alike. It is well illustrated, with high quality original photographs, and includes distribution maps, figures and tables.